Simulation of body temperature and different gaseous phase on in vitro maturation and embryo development in goat - SINGH, R K; DAS, B C; MAJUMDAR, A C; BAG, SADHAN (The Indian Journal of Animal Sciences, 2011)
The present study was carried out to study the effect of different simulation of body temperature during in vitro culture along with different gaseous phase on in vitro oocyte maturation, fertilization and embryo development in goat. Goat oocytes were aspirated from ovaries collected from a local slaughterhouse. The oocytes were matured in TCM-199 with HEPES, 10% FBS, 10% follicular fluid, 0.5 μg/ml FSH, 10 IU/ml LH, 0.5 μg/ml estradiol for 27h. The mature oocytes were fertilized with freshly ejaculated sperm in TALP media and cultured in mSOF media without any cell supplementation. The in vitro maturation, fertilization and culture (IVMFC) were done at different gas phases (5% CO2- 20% O2; 5% CO2 - 10% O2; 7.5 CO2 - 20% O2; 7.5% CO2, - 10% O2) at 38.5°C in CO2 incubator with maximum humidity. The study indicated that comparatively better maturation rate., cleavage rate, development of 4–8 cell and morula stage embryos were observed at 39.5°C irrespective of gas phase. Similarly, the better maturation rate was observed in 5% CO2 and 10% O2, whereas better cleavage rate and morula were observed in 5% CO2 and 20% as compared to other gas phases.